Kusmi lac production in Central Narmada valley, Madhya Pradesh, facts and factors - Namdev, Brajesh Kumar; Thomas, Moni; Kurmi, Anil (Indian Journal of Plant Protection, 2026)
The study was conducted in district Narmadapuram of the state of Madhya Pradesh, India during the year 2017-2018. This district is located in the ‘Central Narmada valley’ agro-climatic zone and is known for its agricultural production. In order to gather data, seven villages were selected from the district, with ten farmers from each village chosen for the study. After analyzing the data, it was found that the fresh and dry weight of the Jethwi crop, Oleosa tree was significantly higher than that of Agahni crop. However, despitethis difference, it was observed that this attribute did not contribute to an increase in overall yield from the tree. Interestingly, it was noted that the yield per plant and yield per foot stick were higher in Jethwi crop, but these differences were not statistically significant.